Application of Al-Wa An-Nazhair's Rule of Tarjamah Tafsiriyah on the word adz-dzikr in the translation of the Ministry of Religion of the Republic of Indonesia - Eko Sedayu; Fuadi; Andri Nirwana AN (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This study aims to reveal the application of the rules of Al-Wujuh Wa an-Nazhair in tafsiriyah tarjamah to the word